2019
DOI: 10.2337/db19-0423
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Fatty Acid Oxidation, Endoplasmic Reticulum Stress, and Apoptosis in Left Ventricle of Patients With Type 2 Diabetes

Abstract: Chronic heart failure is a common complication in patients with type 2 diabetes mellitus (T2DM). T2DM is associated with disturbed metabolism of fat, which can result in excessive accumulation of lipids in cardiac muscle. In the current study, we assessed mitochondrial oxidation of carbohydrates and fatty acids, lipid accumulation, endoplasmic reticulum (ER) stress, and apoptosis in diabetic left ventricle. Left ventricular myocardium from 37 patients (a group of patients with diabetes and a group of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 36 publications
1
40
0
1
Order By: Relevance
“…In experimental diabetic cardiomyopathy, severe ER stress and prolonged UPR ER activation contribute to cardiomyocyte apoptotic death [90,91]. In line, markers of ER stress (GRP78 and CHOP) and apoptosis (cleaved caspase-3) were elevated in myocardium of diabetic patients [92].…”
Section: Alterations Of Interactions Between the Er And Mitochondria mentioning
confidence: 84%
“…In experimental diabetic cardiomyopathy, severe ER stress and prolonged UPR ER activation contribute to cardiomyocyte apoptotic death [90,91]. In line, markers of ER stress (GRP78 and CHOP) and apoptosis (cleaved caspase-3) were elevated in myocardium of diabetic patients [92].…”
Section: Alterations Of Interactions Between the Er And Mitochondria mentioning
confidence: 84%
“…The relative contribution of these lipid intermediates to insulin resistance and altered mitochondrial function remains to be elucidated, and in particular it is not clear whether lipid intermediates accumulate in cardiac tissues at sufficient levels to induce insulin resistance and alter mitochondrial function. It was recently reported, however, that the diabetic heart exhibits a decreased mitochondrial capacity for β‐oxidation and increased accumulation of intracellular lipids, even in the absence of contractile failure . Depending on nutritional status and metabolic state, concentrations of lipid intermediates vary significantly.…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolism mentioning
confidence: 99%
“…It was recently reported, however, that the diabetic heart exhibits a decreased mitochondrial capacity for β-oxidation and increased accumulation of intracellular lipids, even in the absence of contractile failure. 85 Depending on nutritional status and metabolic state, concentrations of lipid intermediates vary significantly. The DAG content in control animal hearts varies from 50 to 800 nmol/g.…”
Section: Diacylglycerol-and Ceramideinduced Lipotoxicitymentioning
confidence: 99%
“…SIRT1 is a highly conserved member of the family of NAD + -dependent Sir2 histone deacetylases (Rodgers et al, 2005) and has also been reported to sense the redox shifts and integrate mitochondrial metabolism through post-transcriptional regulation of the transcription factors and histones (Vachharajani et al, 2016). HADHA and HADHB, respectively, encode the α and β subunits of the mitochondrial trifunctional protein, catalyzing the last three steps of mitochondrial beta-oxidation of long-chain fatty acids (Diebold et al, 2019;Ljubkovic et al, 2019) also observed that in diabetic myocardium, a decrease in HADHA reduces the mitochondrial β-oxidation capacity and increases intracellular lipid accumulation, resulting in a negative impact on the heart. Moreover, Vasilescu et al (2018) demonstrated that HADHB is directly associated with severe childhood-onset cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%